Metabolite Profiles and Antioxidant Activity of Dendrobium catenatum Under Simulated Wild Cultivation - Chuyun Guan; Yixin Tang; Qiaoxian Yu; Yanghui Shen; Ying Shi; Pan Wang; Jinping Si; Jingjing Liu (Food Safety and Health, 2026)
ABSTRACT Dendrobium catenatum Lindl., as a medicinal and edible plant, currently relies mainly on greenhouse cultivation, whereas simulated wild cultivation is becoming an important supplement with the popularization of the ecological cultivation concept. A combination of broad‐targeted metabolomics, in vitro antioxidant assay and network pharmacology analysis was used to investigate metabolic differences and antioxidant activities under different cultivation environments. The results showed that the abundance of flavonoids and stilbenoids was significantly upregulated under simulated wild cultivation. In vitro antioxidant assay, the antioxidant activities of leaves and stems under simulated wild cultivation were significantly higher than those under greenhouse cultivation. Molecular docking screening identified a key antioxidant, Denbinobin, which exerts antioxidant activity through multiple pathways and targets. These findings provide a basis for understanding the metabolic differences of D. catenatum under different cultivation environments and also provide references for simulated wild cultivation of other rare and endangered medicinal plants.